Analisis Keseragaman Camber I-Girder pada Proyek Jalan Luar Lingkar Barat (JLLB) Kota Surabaya - Guruh Arief Putra; Made Dharma Astawa; Wahyu Kartini (Jurnal Teknika, 2022)
This research object is a flyover of the Outer West Ring Road (OWRR) Surabaya, with a 50.8m span which will be constructed using precast I-Girder (PCI-Girder). The research concern is applying different prestress design that came from the girder responses into each of inspected objects. The inspected object which are exterior and interior girders will be designed with variation member properties, until we get similar calculated camber. The research will be controlled with range design given by T.Y.Lin and the girder stress governed by SNI 2847:2019. The result of response girder analysis among two object inspected differ about 248,59 kNm. The result of strand analysis for each object are 107 pcs, and 106 pcs. The tendon layout of interior girder getting modified till 75mm. With the specification provided the result of inspected camber calculation are 177,304mm (upward), and 178,459mm (upward) which differ about 1,1545mm. From those we can conclude that camber is similar.